Regional Approaches to Expedited Drug Development and Review: Can Regulatory Harmonization Improve Outcomes?. (November 2018) - Richardson, Elizabeth; Daniel, Gregory; Joy, David R.; Kweder, Sandra L.; Maloney, Diane M.; Raggio, Miranda J.; Jarow, Jonathan P.
Drug regulatory agencies around the world have implemented programs to expedite drug development and review for promising new products for serious diseases. These programs are all intended to minimize delays in patient access to innovative medicines, and have used broadly similar strategies to shorten drug development and review timelines. However, they differ in many key respects, and some stakeholders have suggested that these differences create unnecessary barriers in the development and approval process, possibly leading to delays in access. In collaboration with FDA, the Duke-Margolis Center for Health Policy convened an expert workshop to elicit feedback from a broad range of stakeholders as to whether a lack of harmonization across expedited programs is interfering with the efficient development of new products and, if so, to explore strategies for addressing these challenges. This report provides a summary of key themes and major findings from that discussion.